(untitled) (Journal of Information Technologies in Education (ITE), 2013)
The method of statistic processing of pedagogical experiment for independent excerpts without limitation on the law of distribution of a random variable is developed. The method is based on construction of function of distribution by means of splines. In medium algorithmic language Delfi-7 the program is compiled, helping to construct integral functions of assessment and to test zero hypothesis for arbitrary level of importance. The efficiency of the method is tested by comparison with the results of analysis of the pedagogical experiment for the case of Laplas Law.